Pengaruh Pengembangan Sumber Daya Manusia dan Motivasi terhadap Kinerja Karyawan Golden Tulip Springhill - Cucun Sundari Putri; Desmon Desmon; Armalia Reny WA (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The quality of a good lodging place or hotel will not be separated from the optimal performance of employees. This is in line with the increasing business development causing competition between economic actors in the hospitality sector to be tighter, so to be able to compete companies must pay attention to quality in the field of HR, in order to improve the development of employee performance and optimize all aspects and motivate employees related to company activities. Human resource development is needed so that the level of performance in employees is more creative and innovative. The type of data used in this study is quantitative data collected in the form of respondents' opinions, attitudes, experiences, and other characteristics. When used to determine certain samples and populations, quantitative research techniques can be considered as positivism-based research methodologies based on the results of t tests of human resource development variables and motivation to produce t count greater than t table (1,997) and a Sig value of less than 0.05 This means that there is a partial influence on employee performance that the impact variable between human resource development and motivation has an effect significant to employee performance. As a result, the hypothesis in this study is that together human resource development and motivation have an influence on employee performance.